Effectiveness Test of Ethanol Extract of Petai (Parkia speciosa) on the Number of Atherosclerotic Foam Cells in Male Wistar Rats (Rattus norvegicus strain Wistar) Atherosclerosis Model - Ikhwan Handirosiyanto; Seftiana Khaerun Nisa; Indra Setiawan; Dian Yuliartha Lestari (International Journal of Health Engineering and Technology, 2026)
Atherosclerosis is a chronic inflammatory disease that causes narrowing of the arterial lumen and is a dominant cause of cardiovascular diseases such as myocardial infarction (MI), heart failure, and stroke. Cardiovascular disease itself is the leading cause of death worldwide. Atherosclerosis has a complex pathophysiology, starting from endothelial dysfunction, thickening of the tunica intima, and the formation of atheromatous plaques. During its progression, foam cells are formed, which play a key role in the development of atherosclerosis. The ethanol extract of petai (Parkia speciosa) contains compounds such as flavonoids, saponins, and tannins that function to reduce the levels of Low-Density Lipoprotein (LDL). The purpose of this study was to determine the effectiveness of petai ethanol extract in reducing the number of atherosclerotic foam cells formed in male Wistar rats (*Rattus norvegicus strain Wistar) induced by lard. This study used a true experimental method with a post-test only control group design. A total of 25 rats were divided into five groups: one negative control group, one positive control group, and three treatment groups receiving petai ethanol extract at doses of 100, 200, and 400 mg/kg body weight. The formation of foam cells was observed using a microscope with 400× magnification. Data were analyzed using the One-Way ANOVA test and Post Hoc Tamhane’s test. The results of the One-Way ANOVA test showed a significant difference among the groups (p = 0.000). The Post Hoc Tamhane’s test between the positive control group and treatment groups 1, 2, and 3 indicated significant differences in foam cell formation due to the administration of petai ethanol extract compared to the positive control group (p < 0.05). In conclusion, the administration of petai ethanol extract was effective in reducing the number of atherosclerotic foam cells formed.